Covered TIPS Procedure-Related Major Complications: Incidence, Management and Outcome From a Single Center - Yin, Xiaochun; Gu, Lihong; Zhang, Ming; Yin, Qin; Xiao, Jiangqiang; Wang, Yi; Zou, Xiaoping; Zhang, Feng; Zhuge, Yuzheng (Frontiers in Medicine, 2022)
Background and Objective Transjugular intrahepatic portosystemic shunt (TIPS) is a well-established procedure for treating complications of portal hypertension. Due to the complexity of anatomy and difficulty of the puncture technique, the procedure itself might brought potential complications, such as puncture failure, bleeding, infection, and, rarely, death. The aim of this study is to explore the incidence, management, and outcome of TIPS procedure-related major complications using covered stents. Methods Patients who underwent TIPS implantation from January 2015 to December 2020 were recruited retrospectively. Major complications after TIPS were screened and analyzed. Results Nine hundred and forty-eight patients underwent the TIPS procedure with 95.1% (n = 902) technical success in our department. TIPS procedure-related major complications occurred in 30 (3.2%) patients, including hemobilia (n = 13; 1.37%), hemoperitoneum (n = 7; 0.74%), accelerated liver failure (n = 6; 0.63%), and rapidly progressive organ failure (n = 4; 0.42%). Among them, 8 patients died because of hemobilia (n = 1), accelerated liver failure (n = 4), and rapidly progressive organ failure (n = 3). Conclusion The incidence of major complications related to TIPS procedure is relatively low, and some of them could recover through effective medical intervention. In our cohort, the overall incidence is about 3%, which causes 0.84% death. The most fatal complication is organ failure and hemobilia.